Principles of Marine Bioacoustics - Au, Whitlow W. L.; Hastings, Mardi C.; SpringerLink (Online service) (New York, NY : Springer US, 2008)
Principles of Marine Bioacoustics is about studying the acoustics of marine animals using underwater acoustic techniques. The book discusses and unites the various areas of marine bioacoustics in a single comprehensive text. It covers important subjects associated with marine bioacoustics such as the measurement and generation of underwater sounds, the propagation of acoustic signals in the marine environment and in small tanks, signal processing techniques, and advanced devices used in the field. Also covered are topics relating to marine animals, such as methods to record and acquire acoustic signals from animals, their auditory systems and vocalizations, psychological and physiological testing procedures, and echolocation in marine mammals. This book is aimed at marine biologists and biological oceanographers. It is also relevant for professionals working with government agencies such as the National Marine Fisheries Service or organizations such as the Association of Zoos and Aquariums.
Principles and Methodology -- Measurement and Generation of Underwater Sounds -- Transducer Properties and Utilization -- Acoustic Propagation -- Signal Recording and Data Acquisition -- Fourier Analysis -- Auditory Systems of Marine Animals -- Experimental Psychological and Electrophysiological Methodology -- Acoustics of Marine Animals -- Hearing in Marine Animals -- Emission of Social Sounds by Marine Animals -- Echolocation in Marine Mammals -- Some Signal Processing Techniques -- Some Instrumentation for Marine Bioacoustics Research.
Keywords: LIFE SCIENCES; OCEANOGRAPHY; ANIMAL PHYSIOLOGY; ACOUSTICS; BIOMEDICAL ENGINEERING; LIFE SCIENCES; ANIMAL PHYSIOLOGY; ACOUSTICS; SIGNAL, IMAGE AND SPEECH PROCESSING; OCEANOGRAPHY; BIOMEDICAL ENGINEERING